Optimization of an Automated Arduino-based Dynamic Spray Pyrolysis System - Corpuz, Dawn Christine (Archīum Ateneo, 2019)
Spray pyrolysis is used to produce transparent conducting electrodes, an important component in making solar cells. In this research, an existing automated Arduino-based static spray pyrolysis system is modified into a dynamic spray pyrolysis system using a RepRap Arduino Mega Pololu Shield (RAMPS). Additional stepper motors for the nozzle movements are incorporated to add x-y movements to the nozzle, thus making it behave like a printer. The set-up was improved by incorporating an optimization algorithm based on an existing Design of Experiments (DOE) technique design to produce uniform films. Eight (8) experiments were done, which composes of varied spray pyrolysis parameters – such as dry time, number of passes or layers, dispensing rate of the liquid precursor, and the printing pattern, for the optimization of the set-up.